Exploring the contribution of clinical placement to student learning: A sequential mixed methods study. (June 2022) - Moroney, Tracey; Gerdtz, Marie; Brockenshire, Naomi; Maude, Phil; Weller-Newton, Jennifer; Hatcher, Deborah; Molloy, Luke; Williamson, Moira; Woodward-Kron, Robyn; Molloy, Elizabeth
Abstract: Background: Increasing demand and limited supply of clinical placements in nursing underscore the need to better understand the role of clinical placements in students' learning. Identifying pedagogically rich activities that support work place learning alongside factors that influence educational outcomes has the potential to optimise professional placement experiences. Objective: To explore student nurses perceptions of the value of nursing clinical placements to their learning. Design and methods: A descriptive research design was employed using a sequential mixed method approach. A cross-sectional student survey captured students' perceptions of work integrated learning based on the perceived contribution of a pre-determined list of activities undertaken on clinical placement. Setting and participants: Four Australian universities took part. Participants included students undertaking entry to practice programs. Results: Four hundred and sixty-nine students completed the survey. Thirty-eight students participated in 12 focus groups. Participants rated PRA including interacting and time with patients and performing assessments as the most useful activities. Less useful, were activities that took them away from the patient. Conclusions: To maximise workplace learning, consideration must be given to ensuring students are presented with goal directed activities that support learning and are focused on an expanding scope of practice with opportunities to discuss and engage with staff.